University Social Responsibility: Perspectives From Discourses, Policies, and Management - Carlos Cabanzo; Favio Cala Vitery; Ingrid Fonseca (SAGE Open)
This study aims to analyze the influence of the discourse of international organizations on university social responsibility (USR), from international organizations, in the policy and management frameworks of the State University System in Colombia. Then, we reviewed institutional documents of global and regional organizations, as well as educational policy documents from higher education institutions. Using Atlas Ti. 23 software, our findings indicate that universities adopt the models proposed by international organizations with different approaches. The policy and management frameworks, aligned with François Vallaeys’“impact” perspective, emphasize the importance of tangible results. Seven of the universities studied articulate a well-defined USR policy, with most integrating it into extension and outreach processes. We conclude that USR should be related to education, initiative integration, management, research, organizational culture, and management indicators. We recommend further studies on how USR policies are integrated in higher education institutions.